Dietary Patterns and cardiovascular biomarkers in Adults with and without type 1 diabetes mellitus - Oliveira , Valzimeire do Nascimento de; Nogueira, Valéria Cristina; Ramos, Lorena Taúsz Tavares; Souza , Ana Priscilla Silva de; Machado , Soraia Pinheiro; Nogueira , Isadora Vasconcelos; Júnior, Renan Magalhães Montenegro; Holanda, Marcelo Oliveira; Silva, Ana Paula Apolinário da; Guedes, Marial Izabel Florindo (Seven Editora, 2023)
To identify dietary patterns and assess their association with the presence or absence of type 1 diabetes (T1D) and biochemical markers of cardiovascular risk. The study involved patients with T1D and healthy individuals (n=90). Patients with T1D were recruited at the Endocrinology and Diabetes Outpatient Clinic of the Hospital from the Federal University of Ceará (HUWC-UFC) and healthy adult individuals were recruited at the State University of Ceará (UECE) and UFC, in the period from 2016 to 2017. Dietary intake was obtained through 24-hour recalls. Dietary patterns were identified by principal component factor analysis, followed by orthogonal varimax rotation. Poisson regression estimated the prevalence ratios of independent variables about outcomes. Three main patterns were identified: prudent (poultry, fish, tame fruits, whole grains, vegetables, fruits, skimmed milk, and with a negative charge for beef, pork, cereal, legumes, and whole milk), snack (sandwich and fruit smoothie) and western (industrialized drinks, sweets, snacks, and foods rich in fats). The association was observed between the prudent pattern with lower HDL cholesterol levels; the snack pattern with lower fasting blood glucose and higher triglyceride level and the western one with higher fasting blood glucose levels. There was no association between patterns and the presence or absence of T1D. The patterns identified were not associated with the presence or absence of T1D, but have been related to HDL cholesterol, triglycerides, and blood glucose. DOI:https://doi.org/10.56238/alookdevelopv1-107